Komunikasi Dakwah Komunitas Perempuan Pekerja Migran di Malaysia - Hasniar Rofiq; Luluk Fikri Zuhriyah; Abdul Muhid (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2022)
In pursuit of Islamic knowledge, Muslim women migrant worker create religious spaces where they can express their religiosity. In Malaysia, there are communities that specifically support Indonesian migrant workers, especially Muslims, including female migrant workers. One of the functions of the community is as a means of da’wah to Indonesian migrant workers. The purpose of this study was to explore the communication of da'wah in the Muslim community of women migrant workers in Malaysia. This research is qualitative in nature. The data of this study were analyzed based on Grounded Theory (GT). Data were collected through observation and semi-structured interviews conducted virtually. Then, it is analyzed through different coding stages, namely: open, axial, and selective. The results show that the communication in producing Islamic knowledge in the Muslim community is more informal, less traditional, and more interactive than the way Islamic knowledge is produced in mosques, Islamic organizations, and central IPMI. This community gives women the space to show religious autonomy as well as the production and transmission of Islamic knowledge for influencing the members' behavior. The process of changing behavior that occurs in the form of conformity, social facilitation, and polarization. These three forms of influence take place both in the dimensions of knowledge, belief, ritual, experience and religious commitment.